Suggestion for new 4.4 mm pubo-femoral distance cut-off value for hip instability in lateral position during DDH screening - Husum, Hans-Christen; Hellfritzsch, Michel B; Hardgrib, Nina; Møller-Madsen, Bjarne; Rahbek, Ole (Acta Orthopaedica, 2018)
Background and purpose — Current selective screening algorithms for developmental dysplasia of the hip (DDH) are insufficient. Universal screening programs have been proposed but so far have been deemed too expensive and time consuming. The pubo-femoral distance may solve this problem as a quick, low-cost, highly sensitive, and specific sonographic measurement for DDH, but this has only been validated in the supine position. Therefore we validated pubo-femoral distance (PFD) in the lateral position as an indicator for instability of the hip. Methods — All participants had undergone ultrasonographic diagnostics using the modified Graf technique. In addition, PFD measurements in lateral position were performed. Results were compared between 25 infants who had been treated for DDH because of dysplastic appearance on ultrasound combined with clinical instability and a control group consisting of 100 untreated infants screened for DDH. Sensitivity, specificity, and cut-off points were determined using Receiver operating characteristics (ROC) analysis. Results — We found a mean PFD of 6.8 mm (6.2–7.4) in the treated group with a control group PFD of 3.4 mm (3.3–3.6) (p < 0.005). A PFD value above a threshold of 4.4 mm yielded a sensitivity of 100% and a specificity of 93% for detecting unstable DDH. Interpretation — PFD measured in lateral position was statistically significantly increased in hips of children treated for DDH with Denis Browne hip brace compared with healthy children with unaffected stable hips. Furthermore, the PFD measurement had a high level of sensitivity and specificity at a cut-off value of 4.4 mm. A cut-off value of 6.00 mm has previously been reported as the gold standard in supine position. We suggest that 4.4 mm is used in lateral position.